Magnetic susceptibility as a direct measure of oxidation state in LiFePO4 batteries and cyclic water gas shift reactors. Issue 30 (14th August 2015) - Kadyk, Thomas; Eikerling, Michael
<x xml:space="preserve">Abstract</x> Correlating the magnetic susceptibility to the oxidation state of the porous active mass in a chemical or electrochemical reactor.